Transformasi Pendidikan Agama Kristen: dari Masa Lalu Hingga Masa Kini - Elwira Simamora; Imelda Tambunan; Sani Bancin; Samsul Lumbanraja (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
Christian religious education has a long history rooted in the teachings of Christ. In its development, this education does not only focus on theological doctrine, but also includes social and cultural norms that are relevant to the times. This article discusses the transformation of Christian religious education from traditional dogmatic methods to a more inclusive, interactive, and contextual approach along with the influence of globalization and technological advances. Significant changes have occurred in the curriculum which now integrates contemporary topics such as ethics and interfaith dialogue. More participatory teaching methods and the use of digital media are also described as responses to modern challenges such as secularism and individualism. This article also highlights the important role of Christian religious education institutions, such as churches, Christian schools, seminaries, and the media, in maintaining the relevance of Christian teachings. Amid global challenges, innovation in Christian religious education is considered crucial to remain relevant and effective in shaping the faith and character of Christians in the future.